A Fair Wage Explanation of Labour Market Volatility - Robert Jump (University of Kent, School of Economics, 2014)
This paper proposes an explanation for observed differences in the business cycle volatility of employment and unemployment across a sample of OECD countries. Using an incomplete markets variant of the fair wage real business cycle model, increases in the gross replacement rate of public unemployment insurance are shown to increase the volatility of employment, and decrease the volatility of real wages, ceteris paribus. For a sample of 14 OECD countries over the period 1985-2005, the gross replacement rate is found to be positively correlated with the business cycle volatility of hours worked, lending support to the argument. A secondary contribution, which may be of some use in the incomplete markets literature, is the simple manner in which unemployment is endogenised in the model.
Keywords: E24; E32; J64; J65; 330; Fair Wages; Unemployment; Incomplete Markets